2017
DOI: 10.1038/s41598-017-05849-1
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and latent CMV infection impact on maturation, differentiation and exhaustion profiles of T-cell receptor gammadelta T-cells

Abstract: Ageing is a broad cellular process, largely affecting the immune system, especially T-lymphocytes. Additionally to immunosenescence alone, cytomegalovirus (CMV) infection is thought to have major impacts on T-cell subset composition and exhaustion. These impacts have been studied extensively in TCRαβ+ T-cells, with reduction in naive, increase in effector (memory) subsets and shifts in CD4/CD8-ratios, in conjunction with morbidity and mortality in elderly. Effects of both ageing and CMV on the TCRγδ+ T-cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 72 publications
2
44
0
Order By: Relevance
“…Interestingly, a shift towards more effector phenotypes, largely maintained TCR diversity and a change in Vγ/Vδ usage has also been detected in the peripheral blood of humans upon organismal ageing , suggesting similar age‐related processes occurring in the murine and human γδ T‐cell pool.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, a shift towards more effector phenotypes, largely maintained TCR diversity and a change in Vγ/Vδ usage has also been detected in the peripheral blood of humans upon organismal ageing , suggesting similar age‐related processes occurring in the murine and human γδ T‐cell pool.…”
Section: Discussionmentioning
confidence: 86%
“…faster, suggesting a memory-like phenotype. 113 In sum, results from in vitro and natural infection studies suggest an important role for cd T cells in controlling influenza, HIV and CMV viral replication. 111,112 These results suggest that cd T cells are important mediators of protection against CMV and support approaches using adoptive transfer of effector/memory cd T cells or targeting cd T cells in future CMV vaccine trials.…”
Section: Viral Infectionsmentioning
confidence: 97%
“…The possibility of inducing exhausted cd T cells would need to be considered, however, as CMV infection has both been shown to result in higher numbers of these cells. 113 In sum, results from in vitro and natural infection studies suggest an important role for cd T cells in controlling influenza, HIV and CMV viral replication. Targeting cd T cells through stimulation could provide an important adjuvanttype role in vaccination and/or cure-related strategies for viral infections.…”
Section: Viral Infectionsmentioning
confidence: 97%
“…Using these surface markers, αβ T cells are known to have a higher frequency of highly differentiated and replicative senescent T cells in circulation with aging, denoted by the surface marker CD57 that implies impairment in their ability to proliferate [118]. However, our recent studies, along with others, have shown that while pan-γδ T cells do not express the same phenotypic changes as αβ T cells during aging [119,120]; the frequencies of γδ T cell subsets, particularly the Vδ2+ subset, decrease with age after age 30. However, the extent of the latter is influenced by sex and nationality [121][122][123][124] (Figure 3b).…”
Section: Homeostasis Of γδ T Cells In Tissuesmentioning
confidence: 91%